Ecocatastrophe in Donbass Region and its Effect on the Public Administration Entity - Білоус-Осінь, Тетяна Ігорівна; Білоус-Осінь, Т. І.; Билоус-Осень, Татьяна Игоревна; Bilous-Osin, Tetiana I.; Козачук, Діана Анатоліївна; Козачук, Д. А.; Козачук, Диана Анатольевна; Kozachuk, Diana A.; Васильківська, Вікторія Владиславівна; Васильківська, В. В.; Васильковская, Виктория Владиславовна; Vasylkivska, Viktoriia V. (Foundation for Enviromental Protection and Research, 2019)
Authors raise an issue of hostilities’ environmental implications in the territory of Donbass as well as the current status of the area where the Joint Forces Operation is taking place. The scale of environmental contamination is shown as well as there has been analyzed the understatement fact of their importance from the direction of the profile state structure and also some unfavorable predictions for a short and middle-term prospect. There has been drawn a conclusion of real critical effect of the current situation on the environmental safety in Ukraine on the whole which requires the adequate legal assessment and the perfection in the sphere of public administration. It is recommended to adopt a single normative-legal act on the management issue in the sphere of environmental implication of Donbas hostilities as well as to establish the Inspection on supervision and control over the environmental situation in the Joint Forces Operation area in the structure of the Ministry of Temporarily Occupied Territories and IDPs.

Автори порушують питання екологічних наслідків бойових дій на території Донбасу, а також сучасного стану району проведення Операції Об’єднаних сил. Показано масштаби забруднення навколишнього середовища, проаналізовано факт заниження їх важливості з боку профільної державної структури, а також деякі несприятливі прогнози на коротко- та середньострокову перспективу. Зроблено висновок про реальний критичний вплив сучасної ситуації на екологічну безпеку в Україні в цілому, що потребує адекватної правової оцінки та вдосконалення у сфері державного управління. Рекомендується прийняти єдиний нормативно-правовий акт з питань управління у сфері екологічних наслідків бойових дій на Донбасі, а також створити Інспекцію з нагляду та контролю за екологічною ситуацією в районі проведення Операції Об’єднаних сил у структурі ООС, Міністерство з питань тимчасово окупованих територій та ВПО.
Bilous-Osin T. Ecocatastrophe in Donbass Region and its Effect on the Public Administration Entity / Т. Bilous-Osin, D. Kozachuk, V. Vasylkivska // Ekoloji. - Issue 107. - Foundation for Enviromental Protection and Research, 2019. - P. 6007-6011.
Keywords: atmospheric air pollution; waste products and hazardous chemical agents management; ecocatastrophe; Donbass; the Joint Forces Operation (JFO); damage to the environment; public administration; executive authority body; normative-legal act (NLA); забруднення атмосферного повітря; поводження з відходами та небезпечними хімічними речовинами; екокатастрофа; Донбас; Операція Об'єднаних сил (ООС); шкода довкіллю; державне управління; орган виконавчої влади; нормативно-правовий акт (ООС); Research Subject Categories::LAW/JURISPRUDENCE